2014
DOI: 10.1021/nn500277y
|View full text |Cite
|
Sign up to set email alerts
|

Transient Absorption Microscopy of Monolayer and Bulk WSe2

Abstract: We present an experimental investigation on the exciton dynamics of monolayer and bulk WSe2 samples, both of which are studied by femtosecond transient absorption microscopy. Under the excitation of a 405 nm pump pulse, the differential reflection signal of a probe pulse (tuned to the A-exciton resonance) reaches a peak rapidly that indicates an ultrafast formation process of excitons. By resolving the differential reflection signal in both time and space, we directly determine the exciton lifetimes of 18±1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
192
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(221 citation statements)
references
References 59 publications
26
192
1
2
Order By: Relevance
“…Although theory predicts a long lifetime for the valley polarization, recent studies observe a non-negligible decoherence [200], which points towards other reasons than magnetic impurities as the origin of the spin-flip. Experimental studies have been undertaken to identify the reasons of decoherence of valley polarizations [201,170,202,203,199]. The analysis of the time-dependent optical response of single-layer MoS 2 supported in several substrates or suspended in vacuum can give a hint [170] of how the environment can alter the electronic structure and hence the valley polarization.…”
Section: Spin-orbit Interaction and Valley Physics In Mosmentioning
confidence: 99%
“…Although theory predicts a long lifetime for the valley polarization, recent studies observe a non-negligible decoherence [200], which points towards other reasons than magnetic impurities as the origin of the spin-flip. Experimental studies have been undertaken to identify the reasons of decoherence of valley polarizations [201,170,202,203,199]. The analysis of the time-dependent optical response of single-layer MoS 2 supported in several substrates or suspended in vacuum can give a hint [170] of how the environment can alter the electronic structure and hence the valley polarization.…”
Section: Spin-orbit Interaction and Valley Physics In Mosmentioning
confidence: 99%
“…Reflection contrast [34][35][36], transient absorption [35], time-integrated photoluminescence (PL) [37,38] and time-resolved photoluminescence (TRPL) [39,40] experiments, have been performed to study the emission properties of WSe 2 . In prior studInfluence of the substrate material on the optical properties of tungsten diselenide monolayers 2 S Lippert et al ies on WSe 2 , layers were deposited on SiO 2 /Si substrates [41,42], sapphire [43,44], graphene [45], and fused silica (quartz) [34,46] or sandwiched between layers of hBN [47].…”
Section: Introductionmentioning
confidence: 99%
“…2 A number of exciton decay mechanisms have been suggested as possible underlying processes in previously published studies [31][32][33][34][35][36][37][38][39][40][41][42][43] . For instance, some experiments 36,40 show that the fast decay dynamics (< 50 ps) are dependent on the exciton density and exciton-exciton annihilation is the dominating decay channel, while other studies 33,34,41 show no significant variation in the decay dynamics with the excitation density and that trapping by surface defect states is the responsible process.…”
Section: Resultsmentioning
confidence: 99%
“…The studies on exciton dynamics [31][32][33][34][35][36][37][38][39][40][41][42][43] have shown considerable discrepancy in the interpretation of the exciton dynamics and the specific time scales due to the differences in samples and measurement conditions such as the excitation energy, excitation density, temperature and polarizations. Particularly, the dependence on the excitation density can provide crucial evidence in determining the decay mechanism.…”
Section: Resultsmentioning
confidence: 99%